Analisis Kemampuan Kreativitas Siswa dalam Karya Gambar Kolase pada Pembelajaran Seni Budaya dan Prakarya: Penelitian Kualitatif Deskriptif pada Siswa Kelas 2 SDN Percobaan - Chairunissa, Chairunissa; Komariah, Komariah; Hidayah, Nurul (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research was to describe students' creativity abilities in making collage drawing in Arts and Crafts learning and the results of students' creativity in making collage drawing in Arts and Crafts learning. This research used a qualitative approach with a descriptive method. The subjects in this research were 35 students of grade 2 of SDN Percobaan. Data collection techniques were carried out through observation, interviews, and documentation activities. The data analysis technique used is to collect data and information from observation, interview and documentation, conduct data centers, conduct data presentation to the conclusion of withlug. The results of the study show that students' creativity abilities in making collage works in Arts and Crafts learning can be seen based on all aspects of creativity. The results of the research also show that the results of students' creativity abilities based on the collage works produced are classified as very good. The creativity abilities assessed based on aspects of creativity are fluency, flexibility, originality, and elaboration as well as performance assessment and product performance assessment. The ability of the creativity aspect of flexibility and evaluation of suitability with the theme was successfully achieved by all students. So that Arts and Crafts learning activities using collage media can show students' diverse creativity abilities